2011
DOI: 10.2355/isijinternational.51.1788
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Dissolution in the CaF2–CaO–SiO2 System

Abstract: The hydrogen solubility in the CaF2-CaO-SiO2 slag system has been studied to identify and compare the hydrogen dissolution behavior according to basicity and CaF2 content at high temperature of 1 823 K. The hydrogen solubility typically increases with higher CaF2 content across the entire compositional range, but its effect is more pronounced at higher basicity. At low basicity, CaF2 seems to slightly polymerize the slag network increasing the available incorporation sites, where hydrogen can attach and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…J-Y. Park, et al 29) is reported that the activation energy of hydrogen dissolution is 177 kJ, while the one in this study is 190 kJ which is in good agreement with the data of Park, et al The reaction mechanism of CH4 decomposition is evidently different between the graphite surface and the slag melt. The reaction in cooperation with slag melt must relate to the phenomena with the hydrogen dissolution into slag.…”
Section: Mechanism Of Ch4 Decomposition and Effect Ofsupporting
confidence: 82%
“…J-Y. Park, et al 29) is reported that the activation energy of hydrogen dissolution is 177 kJ, while the one in this study is 190 kJ which is in good agreement with the data of Park, et al The reaction mechanism of CH4 decomposition is evidently different between the graphite surface and the slag melt. The reaction in cooperation with slag melt must relate to the phenomena with the hydrogen dissolution into slag.…”
Section: Mechanism Of Ch4 Decomposition and Effect Ofsupporting
confidence: 82%
“…Thus, H 2 O can contribute to the silicate depolymerization or polymerization. These mechanisms have been substantiated by experimental correlations and spectroscopic investigations . The slags used in this study can be classified as moderately basic slags.…”
Section: Introductionmentioning
confidence: 58%
“…(2) The Effect of the FeO t Content on the Slag Structure at Fixed CaO/SiO 2 Ratios Using FTIR Our previous work 55,56 showed that the dissolution of hydrogen in slag is affected by the degree of slag polymerization and the number of available reaction sites. This polymerization and slag networking effect was ascertained by FTIR and Raman spectroscopy, similarly to Mysen et al [47][48][49] and McMillan.…”
Section: Resultsmentioning
confidence: 99%